Methodology and analysis of employee structure and remuneration - P. Tomšík; S. Lišková (Agricultural Economics (AGRICECON), 2004)
The paper deals with forming of methodology overview, which could be used for an analysis of employee structure linked to differentiation of remuneration in an enterprise. It suggests an age structure, a structure according to education and qualification, number of employees, permanent state, fiscal state, paid state. The wage differentiation analysis comes from the calculation of month wage and series of quantiles indicators.